INNOVATION AND CHALLENGES IN THE DEVELOPMENT OF BIOSIMILARS: GLOBAL REGULATIONS AND THEIR APPLICATION IN CANCER THERAPY (2025) - Nurvianthi, Riska Yuli; Gisman, Rahmiaty (The SDGS Forum Communication, 2025)
Biosimilars offer a more affordable alternative to reference biologic drugs, providing a solution to reduce treatment costs, particularly in cancer therapy. However, their development faces challenges, especially regarding regulatory differences between countries, which delay their global distribution. This article reviews the latest developments in biosimilar development, particularly in cancer treatment. The primary focus is on the regulatory challenges encountered in the development and distribution of biosimilars, as well as their application in cancer therapy, with emphasis on the acceptance challenges faced by healthcare professionals and patients. This literature review examines recent studies on biosimilars, including regulatory approval processes, clinical applications, and the economic impact on cancer treatment. The analysis also compares regulations across countries and highlights the success of biosimilars in replacing reference biologic drugs such as trastuzumab and rituximab. While innovations in advanced statistical methods have been implemented to expedite the approval process, inconsistent regulations across countries remain a significant barrier. Biosimilars have proven effective in replacing more expensive biologic drugs, but challenges in acceptance by the medical community and patients persist. Some countries have begun accepting biosimilars as alternatives, though regulatory gaps and uncertainties about long-term efficacy continue to pose obstacles. The development of biosimilars has the potential to reduce cancer treatment costs, but regulatory challenges and acceptance by healthcare professionals and patients must be addressed. Further research is needed to explore long-term effectiveness and harmonize global regulations to accelerate biosimilar adoption in cancer therapy.